Cold War Art Worlds: South Asian Art and Artists in Prague, 1947-1989 - Wille, Simone (Leuven University Press, 2025)
Prague as a vital Cold War hub for South Asian artists. During the Cold War, the Central-European capital city Prague, along with other previously less noticed locations in the polarised post-war world, emerged as a key site where an art world of particular importance for artists from South Asia developed. By emphasising cultural mobility as a catalyst for exchange and network building, this book challenges and complicates assumptions about Cold War binaries of East and West and the polarisation between so-called totalitarian regimes and free cultures. Positioning Prague as a nexus where South-Asian modernisms intersected with multiple peoples, histories, and ideologies in the post-World War II era, it offers a narrative of decolonisation that rejected rigid systemic alignment in favour of participation across blocs by prioritising migratory aesthetics over nationalist parochialism. Well-researched and rich in archival materials, this book proposes new ways of writing art histories and makes a significant contribution to both Cold War studies and critical global modernism studies.